Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 194593 by pascal889 last updated on 10/Jul/23

Answered by MM42 last updated on 10/Jul/23

u_n =u_(n−1) +n+1   ;n≥2  ,   u_1 =4  u_n =u_(n−1) +(n+1)        =u_(n−2) +(n)+(n+1)        =u_(n−3) +(n−1)+(n)+(n+1)       ⋮        =u_2 +4+5+...+(n)+(n+1)         =u_1 +3+4+...+(n)+(n+1)  ⇒u_n =4+(((n−1)(n+4))/2)=(n^2 /2)+((3n)/2)+2  ✓

un=un1+n+1;n2,u1=4un=un1+(n+1)=un2+(n)+(n+1)=un3+(n1)+(n)+(n+1)=u2+4+5+...+(n)+(n+1)=u1+3+4+...+(n)+(n+1)un=4+(n1)(n+4)2=n22+3n2+2

Answered by Frix last updated on 10/Jul/23

4+3=7  7+4=11  11+5=16  u_n =(n^2 /2)+((3n)/2)+2  u_(100000) =5000150002

4+3=77+4=1111+5=16un=n22+3n2+2u100000=5000150002

Commented by BaliramKumar last updated on 10/Jul/23

please detail   how to calculate u_n  = (n^2 /2)+ ((3n)/2)+2

pleasedetailhowtocalculateun=n22+3n2+2

Commented by Frix last updated on 10/Jul/23

u_n =c_2 n^2 +c_1 n+c_0   Insert all given pairs (n, u_n ) and solve the  system.

un=c2n2+c1n+c0Insertallgivenpairs(n,un)andsolvethesystem.

Answered by horsebrand11 last updated on 11/Jul/23

 U_n =4+S_(n−1)     U_n =4+((n−1)/2)(6+(n−2).1)    U_n =4+((n−1)/2)(n+4)    U_n =(1/2)(n^2 +3n+4)

Un=4+Sn1Un=4+n12(6+(n2).1)Un=4+n12(n+4)Un=12(n2+3n+4)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com